2020
DOI: 10.1155/2020/5152736
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Novel Herbal Medicine and Omeprazole in the Treatment of Functional Dyspepsia: A Randomized Double-Blinded Clinical Trial

Abstract: Background. The Trachyspermum ammi L. (TA), Anethum graveolens L. (AG), and Zataria multiflora Boiss (ZM) herbal oils are among the most used herbal products in traditional medicine as the antiseptic, anesthetic, carminative, and antispasmodic. However, there are no clinical studies to evaluate the efficacy of the herbs mentioned in the treatment of functional dyspepsia (FD). This study was designed to appraise the efficacy and safety of a novel herbal medicine consisting of ZM, AG, and TA essential oils compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Of these, 359 articles remained for the full-text review, in which 171 studies met inclusion criteria. Finally, 49 RCTs (Azimi et al, 2017;Bordbar, Miri, Omidi, Shoja, & Akhavan, 2020;Bortolotti, Coccia, Grossi, & Miglioli, 2002;Braden, Caspary, Börner, Vinson, & Schneider, 2009;Chen et al, 2020;Chitapanarux, Lertprasertsuke, & Toworakul, 2020;M.-G. Choi et al, 2015;Y. Choi, Kim, Noh, Lee, & Lee, 2020;Dabos et al, 2010;Du, Ming, Chen, & Li, 2014;Eftekharafzali, Zahedi, Mehrabani, Ahmadi, & Tajadini, 2018;Fani et al, 2010;Ghoshegir et al, 2015;Giacosa et al, 2015;Holtmann et al, 2003;Jung et al, 2016;Khonche, Huseini, Mohtashami, Nabati, & Kianbakht, 2017;J.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 359 articles remained for the full-text review, in which 171 studies met inclusion criteria. Finally, 49 RCTs (Azimi et al, 2017;Bordbar, Miri, Omidi, Shoja, & Akhavan, 2020;Bortolotti, Coccia, Grossi, & Miglioli, 2002;Braden, Caspary, Börner, Vinson, & Schneider, 2009;Chen et al, 2020;Chitapanarux, Lertprasertsuke, & Toworakul, 2020;M.-G. Choi et al, 2015;Y. Choi, Kim, Noh, Lee, & Lee, 2020;Dabos et al, 2010;Du, Ming, Chen, & Li, 2014;Eftekharafzali, Zahedi, Mehrabani, Ahmadi, & Tajadini, 2018;Fani et al, 2010;Ghoshegir et al, 2015;Giacosa et al, 2015;Holtmann et al, 2003;Jung et al, 2016;Khonche, Huseini, Mohtashami, Nabati, & Kianbakht, 2017;J.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…It has been reported previously that herbal remedies can be antiinflammatory, favorably modify gut microbiota, balance to (Bordbar et al, 2020;Jung et al, 2016;Lin et al, 1998;Madisch et al, 1999;Rösch et al, 2002;Wang et al, 2017;Zhao & Gan, 2005) Qualitative efficacy 35.25, <.0001, 74% 1.09 [1.02-1.17] 2.41, .02 (M.-G. Choi et al, 2015;Jung et al, 2016;Li et al, 2013;Lin et al, 1998;Liu et al, 2013;Madisch et al, 1999;Rösch et al, 2002;Wang et al, 2017;Zhao & Gan, 2005) Adverse events 14.66, .07, 45% 0.97 [0.75-1.26] 0.23, .82 (Azimi et al, 2017;Bordbar et al, 2020;M.-G. Choi et al, 2015;Jung et al, 2016;Li et al, 2013;Lin et al, 1998;Madisch et al, 1999;Rösch et al, 2002 Choi et al, 2015;Fani et al, 2010;Jung et al, 2016;Li et al, 2013;Liu et al, 2013;Zhao & Gan, 2005) T A B L E 4 Meta-analysis results of sensitive analysis for different outcomes in comparing herbal remedies with placebo or active control Choi et al, 2015;Li et al, 2013;Zhao & Gan, 2005) improve immune function and tolerance, affect central processing of afferent stimuli, and regulate intestinal motility, visceral hypersensitivity, gastric emptying, and lower esophageal sphincter pressure in FD (Y. S. Kim, Kim, Ha, Kim, & Ryu, 2020). By and large, the mechanism of action of most herbal remedies in FD is yet to be known…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Several herbal remedies have been proven effective and safe in FD with comparable outcomes with conventional treatments, and can serve as complementary and alternative medicine, especially when first line therapeutic approaches fail or are inaccessible to patients [ 9 ]. Some herbal oils improve PDS and EPS, and improve gastrointestinal symptom rating scale (GSRS) numbers and quality of life scores [ 15 ]. Herbal treatments show anti-inflammatory effects and contribute to an improvement in the function of gut microbiota, immune system, central stimuli, and intestinal motility in FD [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chinese herbal medicines have been considered an effective alternative to prokinetics, according to a meta-analysis of 28 RCTs showing that Chinese herbal remedies were more effective than prokinetics at reducing the overall symptoms [ 18 ]. A combination of three herbs ( Trachyspermum ammi L., Anethum graveolens L., and Zataria multiflora Boiss) may be important in the treatment of FD, as the essential oils were proven more effective than omeprazole [ 15 ]. Similarly, the Japanese Yukgunja-tang, also known as Rikkunshito, is a mixture of eight herbs that is frequently prescribed in FD [ 19 ], and it was proven more effective in the total clinical efficacy rate in a meta-analysis of 10 studies with 1246 patients, when combined with Western medicine over the use of Western medicine alone [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Celery and ajwain seeds (fruit) have been traditionally used for different gastrointestinal ailments such as abdominal pain/cramp, bloating, indigestion, nausea, vomiting, inappetence, constipation, and reflux [21][22][23][24]. Based on PM textbooks, the powdered mixture of celery and ajwain seeds is a unique treatment for indigestion [20,22,23] and this is while only few recent trials support this recommendation [25,26]. Although there is no exact equivalent of FD in PM [27], the study of the symptoms of PDS showed that the mixture of Apium graveolens L. and Trachyspermum copticum (L.) Link can be traditionally used for the treatment of similar symptoms in PM [20,25,28].…”
Section: Introductionmentioning
confidence: 99%